Factors determining bone mineral density and trabecular bone score in young women with hyperandrogenism - Elżbieta Sowińska-Przepiera (Journal of Education, Health and Sport, 2017)
TBS seems to be more a reliable determinant of bone quality in patients with this condition, since contrary to BMD, it is less susceptible to confounding effects of altered hormonal and metabolic parameters.